Ultrafast laser processing of glass waveguide substrates for multi-fiber connectivity in co-packaged optics - Grenier, Jason R.; Brusberg, Lars; Wieland, Kristopher A.; Matthies, Juergen; Terwilliger, Chad C. (Advanced Optical Technologies, 2023)
High bandwidth demanding applications such as high-performance computing and hyperscale datacenters are drivers for co-packaged optics, which aims to bring optical signals as close as possible to the electrical computing chips by integrating the electro-optic transceivers and ASICs on the same package substrate. These next-generation switches require advanced fiber-to-chip connectivity and novel packaging concepts to enable sufficient power and cost savings. As such, low-loss, high bandwidth, and high fiber-counts are required at the photonic chip interface. In this work, these challenges are addressed by enabling the multi-fiber push-on (MPO) interface at the edge of integrated glass waveguide substrates and thus leverages the existing fiber connector eco-system. An ultrafast laser process is used to singulate glass wafers into individual photonic chips leaving optical-quality end-facets with <1 μm flatness over the 6.5 mm wide connector region thereby directly enabling low-loss fiber-to-chip edge-coupling. To overcome the high-costs and complex photonic packaging associated with active alignment of the fiber connectors to the glass waveguide interfaces, ultrafast laser-ablated features are accurately positioned on the glass substrate to enable self-alignment of the MPO connector guide-pins resulting in a passive alignment approach. Subsequent mating and de-mating of the MPO connector to the glass waveguide interface yields on average a 0.19 dB increase in the coupling loss compared to using active alignment.